Scope and Possibilities of Production and Marketing of Aromatic Oils with Respect to Globalizing World - Shankar, Tara (Indian Journal of Marketing, 2005)
India is blessed with many positive factors, which enables it to stand at a unique position in agriculture-based products. After achieving self-dependence in agriculture, India is in a position whereby it has become the net exporter of agriculture based products. Aromatic plants are a very important part of agriculture and have been grown in India for their fragrance and therapeutic use from ages. In last four decades due to efforts of Universities and industrial houses many crops could be cultivated on a large scale and many of them have achieved stupendous success. Mint is the very live example of it, which made India no. 1 producer of the same driving away very strong competing country like China and Brazil. Many advanced countries like Germany and Japan with very strong production base of synthetics are finding it very difficult to compete on price and quality with Indian produced natural Menthol. This shows very clearly that if planned efforts are put India can be no. 1 player in this field with very strong position in agriculture fields which can be considered as "LABORATORY UNDER SUN". There is urgent need for strategy and planning for the essential oil segment so that we can achieve this goal. Here, first we have to take in consideration competition from synthetic materials, which are derived from turpentine, and petroleum feed stock like isoprene. These materials are processed on a very large scale so economy of scale favors final prices of this synthetic derived molecule at present compared to its equivalent natural isolates. However, we should take in consideration following factors for future, which can favour production of these isolates, derived from natural essential oils.